2022
DOI: 10.3390/ma15031039
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Electrical and Thermal Properties of Granite under the Application of Electrical Pulses Using Equivalent Circuit Models

Abstract: Since energy efficiency in comminution of ores is as small as 1% using a mechanical crushing process, it is highly demanded to improve its efficiency. Using electrical impulses to selectively liberate valuable minerals from ores can be a solution of this problem. In this work, we developed a simulation method using equivalent circuits of granite to better understand the crushing process with high-voltage (HV) electrical pulses. From our simulation works, we calculated the electric field distributions in granit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…It can be seen from Figure 8 that under the same normal stress condition, the peak shear strength decreases with the increase in λ value. This indicates that the greater the strength difference between the two sides of the rock joint, the worse the shear capacity of the rock joint [ 27 , 28 ]. With the same λ value, the peak shear strength increases with the increase in normal stress, and the normal stress can effectively improve the shear strength of the rock joint.…”
Section: Test Results and Analysismentioning
confidence: 99%
“…It can be seen from Figure 8 that under the same normal stress condition, the peak shear strength decreases with the increase in λ value. This indicates that the greater the strength difference between the two sides of the rock joint, the worse the shear capacity of the rock joint [ 27 , 28 ]. With the same λ value, the peak shear strength increases with the increase in normal stress, and the normal stress can effectively improve the shear strength of the rock joint.…”
Section: Test Results and Analysismentioning
confidence: 99%
“…Fukushima et al [ 6 , 7 ] reported their studies on the modeling and simulation of electrical disintegration. Fukushima et al [ 6 ] developed a simulation method using equivalent circuits of granite to better understand the crushing process with high-voltage (HV) electrical pulses that have been previously identified as a selective liberation method. Using their simulation works, they calculated the electric field distributions, produced heat and temperature changes in granite when an electrical pulse was applied.…”
Section: The Special Issuementioning
confidence: 99%
“…Zuo et al (2020) modeled insulation cable with equivalent circuit models by considering placing the cable into small fractions of insulation (dielectric) material and discussed the HV direct current influence on insulation cables [14]. Kabir et al (2011) [18] made equivalent circuit models to understand the fine ceramics (ZnO varistors) by considering hundreds of ZnO grains of an average grain size of 1-2 µm to understand the nonlinear I-V (current-voltage) properties of ZnO varistors. Ono et al (2009) [17] calculated the electric-field distribution in composite materials using equivalent circuit models under HV applications.…”
Section: Introductionmentioning
confidence: 99%
“…With the above literature, the importance of considering each mineral to understand mineral liberation under a HV application is clearly identified. Additionally, it is worth noting that the equivalent circuit model analysis has a strong potential to understand the electric pulse comminution [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation